The role of abusive supervision on the relationship between person-job fit and engagement - Robinson, J. (University of Jaffna, 2020)
According to the person job-fit (PJ-Fit) theory, high PJ-Fit leads to positive work outcomes. However, empirical evidence is not always aligned with this theory, and scholars endlessly called for further research to find the reasons for this. Therefore, this study investigates the influence of employees’ person job-fit (PJ-Fit) on their work engagement and the moderating role of abusive supervision on the relationship between PJ-Fit and work engagement. This study was conducted with 114 employees working in public-sector organizations in the northern part of Sri Lanka. Hierarchical multiple regression was employed to analyze the data. Personal and demographical variables (age, gender, marital status, and experience) have been controlled in this study. This study's outcomes indicated that PJ-Fit has a significant (positive) impact on work engagement and the relationship between PJ-Fit and engagement is moderated by abusive supervision. The employees with high PJ-Fit are profoundly engage in their work. However, abusive supervision negatively influences work engagement and weakens the positive impact of PJ-Fit on work engagement. This study extends the literature by investigating the influence of PJ-Fit on work engagement and being the first to introduce the abusive supervision as a moderator on this relationship. This study suggests that recruiting employees who fit well to the job is necessary, but it is not sufficient to make them engage in their work. The Organization needs to take necessary steps to avoid abusive supervision to create an engaged workforce that is a crucial indicator of organizational success
Keywords: abusive supervision; attitudes; engagement; leadership; PJ-fit